Challenges in Treating Acromioclavicular Separations: Current Concepts. Issue 19 (1st October 2018) - Cook, Jay B.; Krul, Kevin P.
Abstract : Injuries to the acromioclavicular joint constitute approximately 3.2% of shoulder injuries. Although the overall goal of treatment continues to be return to activity with a pain-free shoulder, the treatment of acromioclavicular joint separations has been fraught with conflict since the earliest reports in both ancient and modern literature. Accurate diagnosis and classification are important to determine the optimal treatment. Nonsurgical therapy remains the mainstay for treatment of low- and most mid-grade injuries, although recent biomechanical and biokinetic data might suggest that patients are more affected than traditionally thought. High-grade injuries often necessitate surgical intervention, although little consensus exists on the timing or technique. New surgical techniques continue to evolve as more biomechanical data emerge and kinematic understanding improves. Challenges associated with management of this injury abound from diagnosis to reconstruction.